PENGARUH PEMBERIAN SUSU KEDELAI ( GLICINE MAX L. MERR ) PADA WANITA MENOPAUSE YANG BERESIKO OSTEOPOROSIS DI PENGAJIAN IBU – IBU AISYIYAH RANTING MELATI MEDAN - ROBITAH ASFUR; AMELIA EKA DAMAYANTY (LP2MTBM MAKARIOZ, 2021)
Menopause causes a significant decrease in estrogen levels that affect various conditions in the body, one of which ischanges in bone that occur due to low estrogen. Osteoporosis is a progressive chronic bone disorder caused by reducedbone mass and changes in structure in bone microarchitecture tissue that increases the risk of fracture and can reducequality of life, especially in menopausal women. Soy milk contains phytoestrogens so that can relieve menopausalsymptoms. To prove whether there is an influence of soy milk on bone mineral dencity in menopausal women who are at riskof osteoporosis. Experimental study with pre and post test group design. Sampling technique with simple randomization.The sample of 30 postmenopausal women who were given soy milk as much as 250 ml / day for 3 months. Before and afterthe intervention Bone Mineral Dencity (BMD) examination was performed with osteopeni and osteoporosis results.The mean value of BMD before intervention was -2.5833 The mean value of BMD after the intervention was-2.2267 Thedifference in BMD before and after the intervention with p = 0.001. There is an effect of 250 ml / day soy milk on BMD inmenopausal women.